Uniportal thoracoscopic treatment in bronchiectasis patients: preliminary experience - (:unkn) unknown (TERMEDIA PUBLISHING HOUSE LTD, 2019)
Introduction: Bronchiectasis is defined as a permanent and abnormal dilation of the bronchi due to destruction of the bronchial wall. The thoracoscopic approach is represented in the literature by a few reports, and multiple port incisions are observed in these studies. Aim: To investigate the effectiveness and outcomes of the single port video-assisted thoracoscopic surgery (VATS) method in the surgical treatment of bronchiectasis. To our knowledge, this is the first study reporting surgical treatment of bronchiectasis via the uniportal thoracoscopic approach. Material and methods: The medical records of 15 patients undergoing surgery for bronchiectasis between 2013 and 2017 were reviewed. The patients were evaluated with regard to age, gender, duration of symptoms, localization, types and duration of the surgery, presence of pleural adhesion, intraoperative complications, amount of intraoperative bleeding, conversion to open surgery, postoperative drainage amount, chest tube removal time, length of hospital stay, mortality and morbidity, follow-up period, duration of narcotic analgesic usage, pain according to visual analog scale evaluation and satisfaction score. Results: A total of 15 patients initially underwent single port thoracoscopic resection and 14 procedures were completed thoracoscopically. In terms of anatomic resections, 6 patients underwent left lower lobectomy, 4 right lower lobectomy, 1 right upper lobectomy, 1 left lower lobectomy + lingulectomy, 1 right basal segmentectomy and 1 patient underwent lingulectomy. The mean operative time was 137.1 +/- 24.5 min and the mean length of hospital stay was 4.78 +/- 1.52 days. The mean postoperative analgesic requirement was 2.85 +/- 0.66 days. Conclusions: We believe that uniportal VATS is a safe, feasible, and effective technique for selected bronchiectasis patients.
Keywords: video-assisted thoracoscopic surgery; minimally invasive surgery; bronchiectasis; uniportal; ASSISTED THORACIC-SURGERY; SURGICAL-MANAGEMENT; LOBECTOMY; RESECTION